Heisenberg Effects in Experiments on Business Ideas - Shelef, Orie; Wuebker, Robert; Barney, Jay B. (Academy of Management Review, 2025)
Prior research on experimental strategy suggests that choices about when and how to experiment on a business idea involve comparing an experiment’s informativeness and cost. Some prior research recognizes that experimenting can also change the appropriable value of a business idea—what this paper calls an experiment’s “Heisenberg effects.” This paper shows that incorporating Heisenberg effects in the analysis of “when” to experiment can profoundly impact recommendations derived from the prior literature that focus only on an experiment’s informativeness and cost. It also shows that actors who experiment will almost always find it advantageous to change the Heisenberg effects of their experiment in deciding “how” to experiment. More broadly, the paper examines how a business idea’s economic potential, an actor’s approach to choosing an experimental strategy, and Heisenberg effects interact in determining when and how actors should experiment.